2023
DOI: 10.1093/sexmed/qfad045
|View full text |Cite
|
Sign up to set email alerts
|

Association between inflammatory indexes and erectile dysfunction in U.S. adults: National Health and Nutrition Examination Survey 2001-2004

Chunhui Liu,
Yue Gao,
Jie Ji
et al.

Abstract: Background The association of inflammatory biomarkers with erectile dysfunction (ED) is still largely unknown. Aim The study sought to explore the association of inflammatory biomarkers with ED in U.S. adults. Methods Participant data for this study were extracted from the National Health and Nutrition Examination Survey, and individuals that lacked informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In an environment predominantly characterized by proinflammatory responses, nitric oxide bioavailability is compromised, resulting in impaired vasodilation. This impairment can be attributed to the suppression of endothelial nitric oxide synthase expression and the overproduction of reactive oxygen species, ultimately leading to endothelial dysfunction [ 17 ] Understanding the intricate interplay between inflammation and ED is crucial for advancing effective treatment strategies and interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an environment predominantly characterized by proinflammatory responses, nitric oxide bioavailability is compromised, resulting in impaired vasodilation. This impairment can be attributed to the suppression of endothelial nitric oxide synthase expression and the overproduction of reactive oxygen species, ultimately leading to endothelial dysfunction [ 17 ] Understanding the intricate interplay between inflammation and ED is crucial for advancing effective treatment strategies and interventions.…”
Section: Discussionmentioning
confidence: 99%
“…When investigating the association between SII and ED, Chunhui Liu et al did not observe any significant relationship in their multivariate logistic regression model. [ 17 ] The inconsistent findings could potentially be attributed to the exclusion of a substantial number of study participants during the analysis of various inflammatory indicators. This limitation may have contributed to the lack of association observed between SII and ED.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were given four options, “almost always or always able”, “usually able”, “sometimes able” and “never able”. Unlike previous definitions of ED through answering the above question as “never able” or “sometimes able” or answering “yes” to the question “Have you ever had ED?” [ 13 , 24 ], herein, a stricter definition of ED was used: Participants who answered “almost always or always able” were identified as having no ED, and the rest were identified as having ED [ 14 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Inflammation not only affects endothelial cells but also contributes to the pathogenesis of metabolic syndromes, all of which promote ED [ 9 ]. Chunhui Liu et al found that the prevalence of ED increased with increasing inflammatory indices [ 13 ]. A study by Youssef MK Farag showed that vitamin D deficiency was independently associated with a higher prevalence of ED and that vitamin D may improve ED through improving inflammation and endothelial function [ 14 ].…”
Section: Introductionmentioning
confidence: 99%